Pengembangan Media Pembelajaran Berbasis Smart Apps Creator pada Mata Pelajaran Informatika Kelas X SMK Negeri 2 Tulungagung - Ardiansyah, Afan Risqi; Indrakusuma, Abdul Haris (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2025)
This research focuses on improving the quality of teaching through the use of varied learning media at SMK Negeri 2 Tulungagung, which implements the Independent Curriculum. Even though technology such as projectors are available, the use of learning media is still dominated by printed books, which has an impact on the decline in students' interest in learning. The problem in learning Informatics at SMKN 2 Tulungagung is the lack of interactive learning media that is technology-based, especially in Computer Network and Internet materials. This research develops technology-based learning media using the Smart Apps Creator Application to increase interactivity and visualization. This study uses the Research & Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the test subjects being students, lecturers as validators of media experts, and teachers as validators of material experts. Data collection instruments include interviews, observations, and questionnaires. The results of media validity obtained a score of 89.5% with the "Very Feasible" criterion and the validity of the material obtained a score of 89.2% with the "Very Feasible" criterion. The small group trial received a score of 76% with the "Feasible" criterion, while the large group trial obtained a result of 84.17% with the "Very Feasible" category. This AR media has proven to be effective in increasing students' understanding and motivation despite several technical obstacles.